Class V Students' Environmental Concern Attitude Through Clean and Healthy Friday Activities - Evia Raihanatun Nabilah; M. Syafruddin Kuryanto; Ika Ari Pratiwi (Jurnal Elementaria Edukasia, 2024)
This research is motivated by the many cases of environmental pollution and careless waste disposal which can trigger environmental damage. Even though the function of the environment is very important in supporting human life. So, a caring attitude towards the environment must be implemented from an early age. This research aims to describe the environmental care attitudes of students at SD Negeri 1 Bantrung through clean and healthy Friday activities. This type of research uses qualitative research with a case study approach. The case study approach aims to comprehensively reveal the values​​of caring character in clean and healthy Friday activities. Data collection techniques use observation, interviews and documentation obtained by researchers during research implementation. This research was carried out at SD Negeri 1 Bantrung. Based on the results of research, students' environmental care attitudes towards the environment are quite good, students can love the surrounding environment with 5 indicators of environmental care attitudes, 4 of which are appropriate, namely saving electricity and water by using enough, the availability of rubbish bins and hand washing facilities available in the area. . in each class, maintain the cleanliness of the school environment by participating in maintaining the cleanliness of the environment, providing bathrooms and sufficient clean water for all school residents. A caring attitude towards the environment is instilled at the educational level through the routine implementation of clean and healthy Friday activities. Clean and healthy Friday activities have a positive impact on caring attitudes towards the environment.